(3QSGdI BaGbjI aj GdYed HGdfSHI GdSJjfjIs
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf hHYO , agPg QSGdI BaGbjI ai GdYed HGdfSHI GdSJjfjI , jYed HgG ai SGFQ GdBaGb , eTJedI Ydi KdGKI YTQ HGHkG GdHGH GdChd (B: (3ai eYQaI GdVQH hGdbSeI (B: (3CONd HCMO GdeVQhHjf JMJ GdBNQ s
(3BNQgG (B:s
(3GdHGH GdKGdK YTQ (B: (3ai eYQaI GdLPQ, hgh Cf JaQb GdeLPhQ eQahYg hefMWg aONdfG HYTQI JMJ YTQI , ahLOfG ai GdHjJ GdeTJQc aGdYTQI ddONhd HgG gi GdLPQ , hYdi gPG GdbjGS , hGddg CYde s
(3Vef eLehY s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3Gdadcs